1995
DOI: 10.1074/jbc.270.30.17866
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Irreversible Binding of β-Funaltrexamine to the Cloned Rat μ Opioid Receptor

Abstract: Binding of beta-funaltrexamine (beta-FNA) to the cloned rat mu opioid receptor expressed in COS-1 cells or Chinese hamster ovary cells was examined. beta-FNA bound to the mu receptor with high affinity. Irreversible binding of [3H]beta-FNA was defined as the binding that could not be dissociated by trichloroacetic acid. Na+ greatly enhanced the specific irreversible binding of [3H]beta-FNA to the mu receptor, which was concentration- and time-dependent. Specific irreversible binding of [3H]beta-FNA was potentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 24 publications
2
43
0
Order By: Relevance
“…m-Opioid receptors in the rat brain were shown to have molecular masses ranging from 60 to 75 kDa, and indicative of a glycoprotein nature that, upon deglycosylation, down-shifts to a sharp band of 39 kDa (for review see Chen et al 1995). The existence of a glycosylated form of the m-opioid receptor was predicted based on previous reports in the literature (in Chinese hamster ovary (CHO) cells and in human embryonic kidney (HEK)-293 cells (Chaturvedi et al 2001)) and on the presence of a typical N-glycosylation consensus sequence located at the N terminus (Chaturvedi et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…m-Opioid receptors in the rat brain were shown to have molecular masses ranging from 60 to 75 kDa, and indicative of a glycoprotein nature that, upon deglycosylation, down-shifts to a sharp band of 39 kDa (for review see Chen et al 1995). The existence of a glycosylated form of the m-opioid receptor was predicted based on previous reports in the literature (in Chinese hamster ovary (CHO) cells and in human embryonic kidney (HEK)-293 cells (Chaturvedi et al 2001)) and on the presence of a typical N-glycosylation consensus sequence located at the N terminus (Chaturvedi et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was centrifuged and the pellets were washed three times by centrifugation and resuspension. Immunoprecipitated materials were dissolved in 2ϫ Lammeli sample buffer and subjected to 8% SDS-polyacrylamide gel electrophoresis (Chen et al, 1995), and 32 P was detected by use of a phosphoimager (Cyclone; PerkinElmer Life Sciences). Quantitation of receptor phosphorylation was performed with the OptiQuant software program.…”
Section: Methodsmentioning
confidence: 99%
“…However, this amino acid might not be a binding pocket for the opioid alkaloids, since using the / receptor chimeras indicated that ␤FNA alkylated amino acids within the region of TM6, e3 loop, and TM7. 83 The irreversible alkylation of the Lys 233 within the opioid receptor apparently was caused by the specific orientation of the fumaramate side chain within the tertiary structure of the receptor.…”
mentioning
confidence: 99%